Understanding global slavery : a reader - Bales, Kevin (Berkeley : University of California Press, 2005)
Slavery continues as a blight on the human world, with an estimated 27 million people around the world in bondage. Kevin Bales undertakes a discussion of the causes of enslavement & the socio-economic factors that sustain slavery in the 21st century.
Understanding slavery today -- Slavery and the human right to evil -- No one shall be held in slavery or servitude : A critical analysis of international slavery agreements -- Slavery and the emergence of non-governmental organizations -- Challenge of measuring slavery -- Globalization and redemption -- Human trafficking : A worldwide concern -- Understanding the demand behind human trafficking -- Coda : three steps to stopping slavery (and four things you can do right away).
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Slavery; Slave labor; Forced labor; Prostitution; Slave trade; Sex Work; Esclavage; Esclaves -- Travail; Travail forcé.; Prostitution; Traite des esclaves; slavery; prostitution; SOCIAL SCIENCE -- Slavery; POLITICAL SCIENCE -- Labor & Industrial Relations; Forced labor; Prostitution; Slave labor; Slave trade; Slavery; Frauenhandel; Menschenhandel; Prostitution; Sklavenhandel; Sklaverei; abolition; academic; antislavery; crime; criminal justice; current affairs; economics; economy; ethics; expose; global economy; global issues; global slavery; globalization; human rights; human trafficking; international; modern slavery; morals; pakistan; phenomenon; politics; race issues; race; racism; redemption; scholarly; servitude; slavery; thailand; true story; us history; Electronic books